X marks the spot: Creating and managing a single service point to improve customer service and maximize resources. Issue 2 (2nd April 2016) - Venner, Mary Ann; Keshmiripour, Seti
ABSTRACT: This article will describe how merging service points in an academic library is an opportunity to improve customer service and utilize staffing resources more efficiently. Combining service points provides libraries with the ability to create a more positive library experience for patrons by minimizing the ping-pong effect for assistance. The Access Services Department at the University of North Texas Libraries was charged with management of the circulation and reference services offered at the service desk. Streamlined planning and modernized management of the desk and its impact on customer service in a changing library environment will be discussed.